2011
DOI: 10.1073/pnas.1103367108
|View full text |Cite
|
Sign up to set email alerts
|

Self-recognition mechanism of MamA, a magnetosome-associated TPR-containing protein, promotes complex assembly

Abstract: The magnetosome, a biomineralizing organelle within magnetotactic bacteria, allows their navigation along geomagnetic fields. Magnetosomes are membrane-bound compartments containing magnetic nanoparticles and organized into a chain within the cell, the assembly and biomineralization of magnetosomes are controlled by magnetosome-associated proteins. Here, we describe the crystal structures of the magnetosome-associated protein, MamA, from Magnetospirillum magneticum AMB-1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 45 publications
4
97
0
4
Order By: Relevance
“…The TPR domain-containing protein MamA was speculated to play a role in activation of biomineralization (5). It was suggested that MamA self-assembles through its putative TPR domain and concave site to form a large homooligomeric scaffold surrounding the magnetosomes (46,47), whereas its convex site interacts with other magnetosome-associated proteins, like MamC, and several unidentified proteins (46,47). However, as in M. magneticum, the deletion of mamA in M. gryphiswaldense had only a weak effect (5), suggesting that these interactions are not essential or can be partly compensated by other proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TPR domain-containing protein MamA was speculated to play a role in activation of biomineralization (5). It was suggested that MamA self-assembles through its putative TPR domain and concave site to form a large homooligomeric scaffold surrounding the magnetosomes (46,47), whereas its convex site interacts with other magnetosome-associated proteins, like MamC, and several unidentified proteins (46,47). However, as in M. magneticum, the deletion of mamA in M. gryphiswaldense had only a weak effect (5), suggesting that these interactions are not essential or can be partly compensated by other proteins.…”
Section: Discussionmentioning
confidence: 99%
“…MamQ (23). MamA forms a multiprotein complex surrounding the magnetosome membrane (47), and MamE is involved in localization of magnetosome proteins by a protease-independent process (32). The heterodimer of the CDF transporters MamB and MamM transports ferrous iron into the magnetosome vesicles (35), and ferric iron is taken up by MamH and MamZ (20) or formed by oxidation of ferrous iron within the vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence, however, suggests that MamI and MamL might be involved in the invagination of the magnetosome membrane, the first step in magnetosome formation (174), although the specific mechanism by which this is mediated remains unclear. The functional domains that have been identified in the remainder of this core set of proteins through in silico and/or experimental evidence include (i) one tetratricopeptide repeat (TPR) (e.g., MamA) that participates in assembly of the magnetosome membrane through protein-protein interactions (203,204), (ii) at least one cation diffusion facilitator (CDF) necessary for iron transport and magnetosome membrane assembly (e.g., MamB and MamM) (205), (iii) PDZ domains that mediate protein-protein interactions (e.g., two in MamE and one in MamP) (174,199,206), (iv) a LemA domain (MamQ) whose function is uncertain (174,199) (207), and (vi) one or two actin-like domains (MamK) involved in magnetosome chain assembly and its positioning inside the cell (164,173). There are also proteins with different multiple domains, such as the protease MamE, which contains trypsin, magnetochrome, and PDZ domains, or MamO, which contains one trypsin domain and one TauE domain (174,199).…”
Section: Genetic Determinants Of Magnetosomesmentioning
confidence: 99%
“…1,11,12 The loss of the magnetosome island leads to a nonmagnetic phenotype of MTB demonstrating its key role in the biogenesis of BMNPs. 11,97,[109][110][111][112][113] Figure 5 shows the participation of proteins of a magnetosome island in the biomineralization of BMNPs in a magnetotactic bacterium. The magnetosome vesicle represents a unique pool providing favorable chemical surroundings for magnetite crystal growth.…”
Section: Biomineralization Proteins Of Mtbmentioning
confidence: 99%